PENINGKATAN KEMAMPUAN PEMAHAMAN MATEMATIS BILANGAN BULAT NEGATIF MELALUI PEMBELAJARAN MATEMATIKA BERSTRUKTUR NUMBER SENSE DI SMP - Bernati, Megasari; Sugiatno, Sugiatno; Yani, Ahmad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractStudents who study mathematics in SMP have mastered basic arithmetic operations. There are some students hampered mastery of basic arithmetic material. The subjects of research is students of grade VIII B SMP. Subject selection is based on random. The instrument used in this research is a matter of mathematical test of mathematical understanding in the form of description, which consists of a matter of pretest and postes. The number of questions as many as 12 items in the form of a description and contains the component Number Sense. Preparation of test questions, begins with the preparation of the grid problem followed by compiling the questions and alternatives key answers each item item. Average score of students' mathematical understanding before being taught the learning of Sense Number structure is 38,93, with details: instrumental understanding included in low category, relational understanding of student is in low category. Whereas after learning structure of Number Sense, average score of student equal to 71,43, with details of student instrumental understanding is in medium category, relational understanding of student is low. Keywords:number sense, mathematical understanding, negative integer, integer.